Risk Factors Contributed to Preterm Birth - Kafi Mohammed Nasir Al Asadi (Kufa Journal for Nursing Sciences)
Background: Preterm labor is labor that happens too early, before 37 completed weeks of pregnancy. Premature birth is also known as preterm birth (or less than 37 weeks-full term is 40 weeks). Important growth and development occur throughout pregnancy especially in the final months and weeks.